Métodos de previsão e determinação de módulo dinâmico de misturas asfálticas aplicadas em rodovias brasileiras - Gouveia, Beatriz Chagas Silva (2016)
The dynamic modulus is a fundamental property that defines stiffness of Hot-Mix Asphalt (HMA), and is a primary material property that serves as an input in mechanistic-empirical pavement design methods. Although well-established worldwide, the dynamic modulus, |E*|, does not have a standard yet in Brazil. Official design methodologies for both new and rehabilitation pavements do not consider this property. As a new national pavement design methodology is under construction, |E*| may be considered as the stiffness parameter of HMA. However, the experimental test to determine |E*| is still not compatible with most national facilities. So the objective of this research is to verify alternative methodologies to the traditional laboratory test. An alternative is to determine |E*| master curve through empirical equations, such as Witczak 1-40D and Hirsch models. In the pursuit of this objective, lab tests were performed on 6 HMA mixtures to evaluate the |E*| according to AASHTO T 342-11. All 6 mixtures, as well as 18 mixtures from secondary data, had their |E*| master curves modeled through Hirsch, Witczak 1-40D, and other equations from the open literature. Experimental master curves were compared to the modeled master curves, in order to test their accuracy. A calibration of one of the evaluated predictive equations was then proposed, which resulted in a simplified equation, well-adjusted to the analyzed data.